Integration of art and technology in personalized radiation oncology care: Experiences, evidence, and perspectives - Casà, Calogero; Dinapoli, Loredana; Marconi, Elisa; Chiesa, Silvia; Cornacchione, Patrizia; Beghella Bartoli, Francesco; Bracci, Serena; Salvati, Alessandra; Scalise, Sara; Colloca, Giuseppe Ferdinando; Chieffo, Daniela Pia Rosaria; Gambacorta, Maria Antonietta; et al. (Frontiers in Public Health, 2023)
Cancer diagnoses expose patients to traumatic stress, sudden changes in daily life, changes in the body and autonomy, with even long-term consequences, and in some cases, to come to terms with the end-of-life. Furthermore, rising survival rates underline that the need for interventions for emotional well-being is in growing demand by patients and survivors. Cancer patients frequently have compliance problems, difficulties during treatment, stress, or challenges in implementing healthy behaviors. This scenario was highlighted during the COVID-19 emergency. These issues often do not reach the clinical attention of dedicated professionals and could also become a source of stress or burnout for professionals. So, these consequences are evident on individual, interpersonal, and health system levels. Oncology services have increasingly sought to provide value-based health care, considering resources invested, with implications for service delivery and related financing mechanisms. Value-based health care can improve patient outcomes, often revealed by patient outcome measures while seeking balance with economical budgets. The paper aims to show the Gemelli ART (Advanced Radiation Therapy) experience of personalizing the patients' care pathway by interventions based on technologies and art. The personalized approach to cancer patients and their role as "co-stars" in treatment care. The paper describes the vision, experiences, and evidence that have guided clinical choices involving patients and professionals in a co-constructed therapeutic pathway. We will explore this approach by describing: the various initiatives already implemented and prospects, with particular attention to the economic sustainability of the paths proposed to patients; the several pathways of personalized care, both from the Patient's and healthcare professional perspective, that put the person's experience at the Gemelli ART Center. The patient's satisfaction with the treatment and economic outcomes have been considered. The experiences and future perspectives described in the manuscript will focus on the value of people's experiences and Patient satisfaction indicators, patients, staff, and the healthcare organization.